Why Don't We Sleep Enough? A Field Experiment among College Students - Mallory Avery; Osea Giuntella; Peiran Jiao (Institute of Labor Economics (IZA), 2019)
Sleep deprivation is a risky behavior prevalent in modern societies, leading to negative health and economic consequences. However, we know little about why people decide to sleep less than the recommended number of hours. This study investigates the mechanisms affecting sleep choice and explores whether commitment devices and monetary incentives can be used to promote healthier sleep habits. Toward this end, we conducted a field experiment with college students, providing them incentives to sleep, and collected data from wearable activity trackers, surveys, and time-use diaries. Our results are consistent with sophisticated time-inconsistent preferences and overconfidence. The subjects in the treatment group responded to the monetary incentives by significantly increasing the likelihood of sleeping between 7 and 9 hours (+19%). We uncover evidence of demand for commitment. Overall, 63% of our subjects were sophisticated enough to take up commitment, and commitment improved sleep for the less overconfident among them. Using time-use diaries, we show that during the intervention, there was a reduction in screen time near bedtime (-48%). Subjects in the treatment group were less likely to report insufficient sleep than at baseline even after removal of the incentive (-16%), which is consistent with habit formation. Finally, our treatment also had positive (albeit small) effects on health and academic outcomes.
Keywords: B49; C93; I1; 330; sleep; health behaviors; sophistication; present bias; habit formation; incentives